Indicateurs et pratiques de gestion de la salinité des sols dans le Gorom-Lampsar (delta du Sénégal) - Ousmane Diouf; Pascal Bartout; Laurent Touchart (VertigO, 2022)
In Senegal, in the agricultural perimeters of the Gorom-Lampsar axis (middle delta of the Senegal River), small agricultural farmers are faced with secondary soil salinization resulting, on the one hand, from the consequences of neoliberal policies initiated in the 1980s, and, on the other hand, of the effects of the absence of assistance from the State in agricultural policy. This situation leads to an absence of an operational management framework, and consequently to poor water management at the small scale of the perimeters. Such management, added to poor development policies which further weaken the control of water use as well as poor drainage and poor disposal of agricultural waste, cause, beyond salinization and the abandonment of land, the destruction of the fragile state of this agricultural space. In this context, farmers use vernacular indicators for recognizing soil salinity and mobilize associated agronomic and hydraulic practices, which are dominated using chemical fertilizers. This promotes better yields in the short term but does not necessarily ensure good management of saline land, which is inherent in water management, which is intended to be operational and strategic.